The Role of Gestalt Counseling in Overcoming Toxic Parents in Children - Gusman Lesmana; Della Puspita; Miftah Afifah Rahmah (Yayasan Zia Salsabila, 2023)
This research discusses the role of Gestalt counseling in responding to and overcoming the psychological impact of children due to toxic parenting. With a focus on a qualitative approach and a case study design, we investigated the experiences of children who had undergone Gestalt counseling sessions in response to their parents' toxic parenting. Data was collected through in-depth interviews, observations, and assessment instruments, with an emphasis on thematic analysis. The research results reveal the positive contribution of Gestalt counseling in helping children integrate their experiences, strengthening emotional well-being, and facilitating behavior change. Practical implications and recommendations for counseling professionals as well as future research directions are also discussed. With a deeper understanding of the role of Gestalt in this context, it is hoped that this research can provide useful guidance in efforts to help children who are exposed to toxic parenting.